Human Resources Development Strategy in Improving the Competence of Functional Education Personnel - Mursidah, Siti; Maskur, Muhammad Azil; Widodo, Mulyo (Management Analysis Journal, 2022)
This study aims to analyze the condition of Functional Human Resources after the transfer of positions and determine the best alternative policy strategies in developing human resources in an effort to increase the competence of staff at UNNES. Equalization of structural positions to functional positions is quite difficult in practice because not all the details of previous tasks are in accordance with the functional positions resulting from the equalization. This research uses a case study approach. This study took the location of UNNES. The analytical tool used to determine the HR development strategy of UNNES uses the Analytical Hierarchy Process (AHP). The survey was conducted on 22 employees who were affected by the transfer of positions from structural to functional positions at UNNES and 3 officials who handled HR issues. Interviews with key persons were conducted to capture perceptions and assessments of key persons on the condition of functional education personnel after the transfer of position functions. The results of the study indicate that the functional staff from the equalization experiences are confused and have not been able to adapt to their main duties and functions. Based on the analysis using the AHP method, it shows that the classical training strategy with the priority of providing opportunities for employees to take part in functional training can help improve HR competencies.